Chemometrics Optimized Extraction Procedures, Phytosynergistic Blending and in vitro Screening of Natural Enzyme Inhibitors Amongst Leaves of Tulsi, Banyan and Jamun - De, B.; Bhandari, K.; Singla, R.K.; Katakam, P.; Samanta, T.; Kushwaha, D.K.; Gundamaraju, R.; Mitra, A. (2015)
Background: Tulsi, Banyan, and Jamun are popular Indian medicinal plants with notable hypoglycemic potentials. Now the work reports cherno-profiling of the three species with in-vitro screening approach for natural enzyme inhibitors (NEW against enzymes pathogenic for type 2 diabetes. Further along with the chemometrics optimized extraction process technology, phyto-synergistic studies of the composite polyherbal blends have also been reported. Objective: Chemometrically optimized extraction procedures, ratios of polyherbal composites to achieve phyto-synergistic actions, and in-vitro screening of NEls amongst leaves of Tulsi, Banyan, and Jamun. Materials and Methods: The extraction process parameters of the leaves of three plant species (Ficus benghalensis, Syzigium cumini and Ocimum sanctum) were optimized by rotatable central composite design of chemometrics so as to get maximal yield of bio-actives. Phyto-blends of three species were prepared so as to achieve synergistic antidiabetic and antioxidant potentials and the ratios were optimized by chemometrics. Next, for in vitro screening of natural enzyme inhibitors the individual leaf extracts as well as composite blends were subjected to assay procedures to see their inhibitory potentials against the enzymes pathogenic in type 2 diabetes. The antioxidant potentials were also estimated by DPPH radical scavenging, ABTS, FRAP and Dot Blot assay. Results: Considering response surface methodology studies and from the solutions obtained using desirability function, it was found that hydro-ethanolic or methanolic solvent ratio of 52.46 +/- 1.6 and at a temperature of 20.17 +/- 0.6 gave an optimum yield of polyphenols with minimal chlorophyll leaching. The species also showed the presence of glycosides, alkaloids, and saponins. Composites in the ratios of 1:1:1 and 1:1:2 gave synergistic effects in terms of polyphenol yield and anti-oxidant potentials. All composites (11 :1, 1:21, 2:1:1, 1:1:2) showed synergistic anti-oxidant actions, Inhibitory activities against the targeted enzymes expressed in terms of IC50 values have shown that hydro-ethanolic extracts in all cases whether individual species or composites in varying ratios gave higher IC50 values thus showing greater effectivity. Conclusion: Current research provides the state-of-the-art of search of NEls amongst three species by in-vitro assays which can be further utilized for bioactivity-guided isolations of such enzyme inhibitors. Further, it reports the optimized phyto-blend ratios so aster achieve synergistic anti-oxidative actions.